Prognostic Value of Resting Left Ventricular Sphericity Indexes in Coronary Artery Disease With Preserved Ejection Fraction - Ping Wu; Yuting Zhao; Xiaoshan Guo; Xia Liu; Yingqi Hu; Yuxin Xiao; Li Xu; Nan Huang; Yuanyuan Li; Yanhui Wang; Tailin Ren; Qiuyan Wu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Adverse left ventricular remodeling is a significant cardiovascular predictor for patients with coronary artery disease and preserved left ventricular ejection fraction (LVEF). However, the remodeling indexes reflecting left ventricular spherization by myocardial perfusion imaging are underexplored. Methods and Results 727 patients (mean age 59.8±13.5 years, 329 women) diagnosed or suspected coronary artery disease with preserved LVEF who underwent resting myocardial perfusion imaging were retrospectively enrolled. The myocardial perfusion imaging findings including the total perfusion deficit and sphericity indexes (shape index (SI) and eccentricity index (EI) obtained from gated (QGS) and non‐gated (QPS) images) were collected. Major adverse cardiovascular events (MACE) were followed up for 45.1±22.0 months. All patients were divided into 4 subgroups based on total perfusion deficit at 10% and LVEF at 65%. Univariable comparative analyses were performed in 5 cohorts (all patients and 4 subgroups). Patients who experienced MACE displayed higher SI and/or lower EI (all P<0.05). Kaplan–Meier survival analyses suggested significant differences for SIQPS in all 5 cohorts, for EIQPS and EIQGS in 4 cohorts, and for end‐systolic and end‐diastolic SIQGS in 3 cohorts (all P<0.05). Multivariate Cox analysis showed that abnormal SI and EI remained statistically significant predictors for MACE after adjusting for total perfusion deficit, LVEF, and other confounding factors. Conclusions For patients diagnosed or suspected of coronary artery disease with preserved or supra‐normal LVEF, resting sphericity indexes by myocardial perfusion imaging displayed incremental long‐term prognostic value. Among these indicators, SIQPS is particularly promising across different perfusion or preserved functional conditions.